Usaha Pembentukan Akhlakul Karimah dI RA Safinatunnaja Kisaran Timur Kab Asahan - Andi Andi; Molek Maydian Astuti (Jurnal Dirosah Islamiyah, 2019)
Andi1, ABSTRACT The formation of noble character in children as one part of the goals of national education is still a problem. Many factors cause this problem, including the lack of roles of parents and teachers in shaping the character of children from an early age. The formation of a child's morality from an early age, it can be seen that a child will be able to display noble character when educators, both parents and teachers, are able to understand the child's psyche while starting to teach and familiarize children with noble character from childhood, and choose a morally healthy environment to the child. This research was conducted to find out: (1) How is the teacher's effort in the process of forming a child's morality through good words RA at RA Safinatunnaja, Kisaran Timur Kab. Asahan, (2) How is the teacher's effort in the process of forming morality through religious activities at RA Safinatunnaja, East Kisaran Kab. Asahan, (3) How is the teacher's effort in the process of forming the morals of children outside of school at RA Safinatunnaja, East Kisaran, Asahan Regency. The results of the study found that the efforts of the teacher to form akhlaq karimah in RA were introduced to students, taught, understood the meaning and importance of forming akhlaq karimah, starting from their words, knowledge and actions. The teacher's efforts in the process of moral formation through outside the school are taught about "Gratitude (thanks for the blessings that Allah has bestowed on humans and all creatures), Qana'ah (feeling enough and willing to give gifts given by Allah Sincerely solely because of Allah, we in class A teach children morality with religious activities, children are taught to be sensitive to the environment, children are accustomed to doing good with the environment by not littering, crossing walls and not making people restless. Keywords: Business, Formation, Akhlakul Karimah